Respostas
respondido por:
0
a1 = 1 , q = 3 , n = 10
fórmula da soma dos termos de um pg, só substitui os dados na fórmula
a1( q^n -1 ) 1( 3^10 - 1 ) / 3 - 1 = 1( 59,049 - 1) = 59.048 = 29.524
q - 1 2 2
fórmula da soma dos termos de um pg, só substitui os dados na fórmula
a1( q^n -1 ) 1( 3^10 - 1 ) / 3 - 1 = 1( 59,049 - 1) = 59.048 = 29.524
q - 1 2 2
gustavocanabarro:
3^10 pode simplificar, é mesma coisa q (3^5 ) ² = 243 ² = 59.049
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás